2023
DOI: 10.21037/qims-22-910
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pathological response evaluation systems after neoadjuvant chemotherapy for breast cancer: developing predictive models of multimodal ultrasound features including shear wave elastography combined with puncture pathology

Abstract: Background: This study created a predictive preoperative nomogram dependent on multimodal ultrasound characteristics and primary lesion biopsy results for various pathologic response assessment systems following neoadjuvant chemotherapy (NAC).Methods: This retrospective study included 145 breast cancer patients treated at Gansu Cancer Hospital between January 2021 and June 2022 who underwent shear wave elastography (SWE) prior to completing NAC. Intra-and peritumoral SWE features, including maximum (E max ), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In addition, several antecedent studies underscore the superiority of pretreatment SWE over ultrasound alone in predicting neoadjuvant chemotherapy response. Furthermore, an artificial intelligence model or nomogram developed by incorporating radiologic parameters from medical images including SWE and clinicopathologic data has exhibited excellent diagnostic predictive performance for the neoadjuvant chemotherapy response [32,33]. These results not only highlight the synergistic potential of various data sources but also emphasize the role of elasticity values as a pivotal factor in accurately predicting the response to neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, several antecedent studies underscore the superiority of pretreatment SWE over ultrasound alone in predicting neoadjuvant chemotherapy response. Furthermore, an artificial intelligence model or nomogram developed by incorporating radiologic parameters from medical images including SWE and clinicopathologic data has exhibited excellent diagnostic predictive performance for the neoadjuvant chemotherapy response [32,33]. These results not only highlight the synergistic potential of various data sources but also emphasize the role of elasticity values as a pivotal factor in accurately predicting the response to neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 82%
“…The association between low elasticity values and a favorable response to neoadjuvant chemotherapy has been consistently represented [30][31][32][33][34][35]. In addition, several antecedent studies underscore the superiority of pretreatment SWE over ultrasound alone in predicting neoadjuvant chemotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…We set the expression of CASP1 as the dependent variable and incorporated the characteristics with P<0.05 as the independent variables into a multivariate analysis through binary logistic single-factor analysis. The results showed that tumor margin ( 25 , 26 ) and blood flow grade ( 21 ) were independent prognostic factors affecting the expression of CASP1 in BRCA (see Table 4 ).…”
Section: Resultsmentioning
confidence: 98%
“…Ultrasound, as a simple, non-radiation, non-invasive, real-time examination technology, is the first choice for screening and diagnosis of female BRCA. Conventional ultrasound, shear wave elastography, and contrast-enhanced ultrasound (CEUS), as commonly used methods for detecting breast lesions, have been widely accepted and recognized by patients and clinical doctors in the diagnosis of breast lesions and the evaluation of chemotherapy efficacy ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%